Target and Non-target Site Mechanisms Developed by Glyphosate-Resistant Hairy beggarticks (Bidens pilosa L.) Populations from Mexico - Alcántara-de la Cruz, Ricardo; Fernández-Moreno, Pablo T.; Ozuna, Carmen V.; Rojano-Delgado, Antonia M.; Cruz-Hipolito, Hugo E.; Domínguez-Valenzuela, José A.; Barro, Francisco; De Prado, Rafael (Frontiers in Plant Science, 2016)
In 2014 hairy beggarticks (Bidens pilosa L.) has been identified as being glyphosate-resistant in citrus orchards from Mexico. The target and non-target site mechanisms involved in the response to glyphosate of two resistant populations (R1 and R2) and one susceptible (S) were studied. Experiments of dose-response, shikimic acid accumulation, uptake-translocation, enzyme activity and EPSPS gene sequencing were carried out in each population. The R1 and R2 populations were 20.4 and 2.8-fold less glyphosate sensitive, respectively, than the S population. The resistant populations showed a lesser shikimic acid accumulation than the S population. In the latter one, 24.9% of 14C-glyphosate was translocated to the roots at 96 h after treatment; in the R1 and R2 populations only 12.9 and 15.5%, respectively, was translocated. Qualitative results confirmed the reduced 14C-glyphosate translocation in the resistant populations. The EPSPS enzyme activity of the S population was 128.4 and 8.5-fold higher than the R1 and R2 populations of glyphosate-treated plants, respectively. A single (Pro-106-Ser), and a double (Thr-102-Ile followed by Pro-106-Ser) mutations were identified in the EPSPS2 gene conferred high resistance in R1 population. Target-site mutations associated with a reduced translocation were responsible for the higher glyphosate resistance in the R1 population. The low-intermediate resistance of the R2 population was mediated by reduced translocation. This is the first glyphosate resistance case confirmed in hairy beggarticks in the world.